Humánerőforrások elvárás vizsgálata különböző ágazatokban - Juhász, Csilla; Vántus, András (Közép-Európai Közlemények, 2012)
Expectancy is one of the main and interesting problem in organizations. The technical background of this survey is constituted of 3 different theories. One of them is the motivational spiral. The other is the motivation sychron modell what illustrates that the succes of the organizational motivation maybe justified by 3 aspect organizational, employers and employees possibilities. Thought provoking were Vroom’s expectancy theorie, which explaines the coherence between work and expectations. And the Cominis- Emanual model which explains the detailes of managerial expectations and motivation. We made a study based on a questionary. In different sectors we asked managers about expectancy of their employees. It was completed with interviews. The questionary was based on expectancy theories. Now we have extended the subject, which included in public utilities, industrial organization, education and armed force. We asked about the eployee’s expectancy, about work, and whose expectancy were important. On the questionary form for this problem were the follows: personal, managerial, contributoral, professional, payment’s, working hours’, technological. Results of examinations of expectations in different sectors revealed that analysis do not show unified evaluation. Some expectational effect are outstandingly important in some sectors but it is not same for other sectors.